The Augmentation of Radical Ideas and the Role of Islamic Educational System in Malaysia - Abdullah, Mohd. Kamarulnizam (Studia Islamika, 2009)
This article analyses how the Islamic educational system in Malaysia, particularly the role played by madrasahs and pondoks,shapes its graduates' perception and mindset. The questions that will be raised are therefore: to what extent does Islamic education in Malaysia contribute to the rise of radical Muslims? What aspects of the teachings, pedagogy and/or curriculum provided in the Islamic educational system is capable of generating feelings of hatred against non-Muslims in Malaysia's multi-religious society. Are there other independent variables that may contribute to, and explain why, the Islamic educational school system has been identified as breeding ground for Muslim terror- ism? The scope of this paper then focuses on the traditional Islamic educational system especially the partially state funded and privately run madrasahs and pondoks.DOI: 10.15408/sdi.v16i1.490